Intramuscular Pressure Following Compartment of Limbs by Electric Measuring Instrument of Tissue Pressure - Paek, Chol-Hyok; Ryang, Ki-Hyon; O, Jong-Hyon; Im, Kum-Chol; Kim, Suk-Yong; Chae, Kwang-Hyon (Medical Science Journal for Advance Research, 2025)
Muscular compartment syndrome that is a surgical disease at high risk of morbidity and disability, causes intra-compartment bleeding as injury of muscle tissue with fracture and luxation in limbs. Increasing pressure of a compartment makes small veins exhausted and migration of humor difficult in that compartment, finally it causes arterial ischemic block of blood circulation and muscular necrosis by increasing tissue pressure that is just opposite of systolic pressure. That is why it is really important to diagnose and treat this disease earlier than irreversible ischemic changes, so we can reduce permanent disability. We used an electric measuring instrument of tissue pressure and obtained some basic results to diagnose those disease that causes increasing disability earlier by measuring intramuscular pressure following compartment in healthy people and patients with closed fracture in their limbs. The difference between every muscles following compartment, sex, age in healthy people was not statistically significant, and difference between sports men and officers or workers reached statistical significance. Intramuscular pressure in fracture region of patients with closed fracture in limbs was statistically significantly higher than a normal region of them.